Surface dissolved nitrous oxide concentrations during SONNE cruise SO305 - Damian L Arévalo-Martínez; Marcel Sommer; Hermann W Bange; Paula Eisnecker; Gesa Schulz; Ina Stoltenberg (PANGAEA, 2025)
The dataset comprises high-resolution (1-min) measurements of dissolved nitrous oxide in surface waters of the Eastern Tropical Indian Ocean. The observations were conducted during the expedition SO-305 on board R/V SONNE (April-May 2024). Seawater was drawn on board by means of a submersible pump installed at 6 m depth, and measurements of equilibrated headspace were carried out as described in Arévalo-Martínez et al. (2013): https://doi.org/10.5194/os-9-1071-2013.